THE ALTERNATIVE MODELS OF REFORM OF UKRAINIAN RAILWAY TRANSPORT - Hrechko, A. V. (Science and Transport Progress, 2008)
In the paper a definition of management mechanism of railway transport enterprises is suggested. On the basis of this definition the basic models of reforming the railway transport of Ukraine are systemized.